Artemisia herba alba Essential Oil: GC/MS analysis, antioxidant activities with molecular docking on S protein of SARS-CoV-2 - Khaoula Diass; Imane Oualdi; Mohammed Dalli; Salah-eddine Azizi; Mounir Mohamed; Nadia Gseyra; Rachid Touzani; Belkheir Hammouti (Indonesian Journal of Science and Technology, 2023)
This study was conceived to work on Artemisia herba alba essential oils (EOs) originating from Eastern Morocco. We investigated the chemical properties and determined the antiradical scavenging activity. The GC-MS technique was used to elucidate the chemical composition of the two studied regions. Jerada Eo was distinguished by the existence of 1,6-Dimethylhepta-1,3,5-triene (36.44%), Camphor (22.50%), and Thujone (7.21%). While, Taourirt EO was found to be rich in Camphor (55.31%), Eucalyptol (14.64%), and Camphene (9.95%). Moreover, the free radical scavenging ability (DPPH•), and ferric reducing power assay (FRAP) were conducted. The EOs tested are found to be weakly active and to have important antioxidant potential. The docking study was also carried out by theoretical investigation with molecular docking of four active predominating components (1,6-dimethylhepta-1,3,5-triene; Chrysanthone; Eucalyptol; Alpha-pinene) against S protein of SARS-CoV‑2, and all the four ligands were found to bind to the S protein 6CS2 of SARS-CoV-2 differently and that the stable complex formed as a result of these interactions may prevent the binding of ACE2 with the spike S protein of SARS-CoV-2.